Phylogeography of Pennella (Copepoda: Siphonostomatoida: Pennellidae) indicates interoceanic dispersal mediated by cetacean and fish hosts - Sofía Ten; Rachel Vanessa Pool; Juan Antonio Raga; Andrew D. Sweet; Francisco Javier Aznar (Parasitology)
Copepods of the genus Pennella parasitize a wide range of marine animals, including cetaceans, teleosts, and cephalopods worldwide. Their taxonomy is unclear, as there is incongruence between morphological and genetic data and incomplete species coverage. This study provides new morphological and genetic (COI) data from 23 specimens of Pennella cf. filosa (syn. P. balaenoptera) from western Mediterranean whales and a swordfish. First, their position in the phylogeny of Pennella was assessed and species delimitation revisited using all available Pennella COI sequences (n = 189), obtained from Mediterranean and north Pacific specimens from 18 host species (including multiple cetaceans and teleosts). Second, it was investigated whether the geographic location, degree of host vagility, or host taxonomic identity help explain genetic differentiation. Five distinct haplotype groups with varying genetic divergence were distinguished. Although the presence of sibling species cannot be ruled out, species delimitation methods could not find interspecific genetic differences, leaving the taxonomy of the genus unresolved. The observed genetic differentiation could not be attributed to geography or host type. This suggests that members of the genus Pennella show low specificity for definitive hosts and interoceanic dispersal mediated by some vagile definitive hosts. The use of more genetic markers for addressing these questions in the future is encouraged.